Półka filmowa 2015 - Agnieszka Tambor (Postscriptum Polonistyczne)
The article presents the summary of the 2015 season of Polish filmmaking. All movies mentioned in the article are chosen and described according to that which would be interesting for a foreigner or a person who studies Polish as a foreign language. The following films are described here: Król życia, Chemia, Obce niebo, Demon, Klub włóczykijów, Panie Dulskie, Disco polo, Listy do M. 2, Moje córki krowy, Mur.